LEXICAL FIELD OF ‘SAYING’ ON JAPANESE LEXEME IU - Gapur, Abdul; Mulyadi, Mulyadi (Universitas Pendidikan Indonesia (Indonesia University of Education), 2018)
The research discusses the lexical semantics words in lexeme iu (è¨€ã†) in Japanese, the lexical relation and the meaning feature, which are found of each word in a semantics field. Lexeme iu (è¨€ã†) is literally interpreted by word â€˜sayâ€™. In kanji (è¨€ã†), there are common meaning and derivative meaning (hyponim and synonym) which form a lexical field. The data are taken from kind of sources such as e-newspapers and scientific journals with limitation for lexeme formed by one kanji letter. As the result of research finds lexical field of Iu in lexemesÂ hanasu, shaberu, kataru, noberu, osharu, tsutaeru, mousu, yobu, tsuku sasou, maneku, benjiru, ronjiru, chikau, chigiru, utau, shou suru, sasayaku, uwasa suru, sakebu, wameku. Lexical field is formed by the lexical relation of synonymy and hyponimy.